New perspectives in biliary tract cancers - T.O. Goetze; C. Roderburg; F.W. Friedrich; J. Trojan (ESMO Gastrointestinal Oncology, 2024)
Biliary tract cancer (BTC) is a rare but highly lethal malignancy. Despite recent advances in diagnosis and treatment, the overall prognosis remains dismal, with a median survival of <1 year in most cases. This highlights an urgent medical need for better treatment options, especially in the area of systematic treatments.This review aims to give a concise overview of the current available treatment options for BTC, including a short summary of longstanding therapeutic approaches such as surgery, interventional techniques, radiotherapy, chemotherapy, and chemoradiotherapy. Special emphasis is placed on genetic alterations and treatment advances with immunotherapy in combination with chemotherapy, however, including current trials on new immunotherapeutic drugs. Furthermore, the recent recommendation by international guidelines to use durvalumab plus the combination of gemcitabine and cisplatin as a first-line treatment in the advanced setting is highlighted and the evidence supporting this recommendation is explored. Moreover, this review looks at genetic alterations which can be used as targets for immunotherapy, especially isocitrate dehydrogenase 1/2 (IDH1/2), fibroblast growth factor receptor 2 (FGFR2), and human epidermal growth factor receptor 2 (HER2/neu). Upcoming biomarkers such as microRNAs (miRNAs and especially miR-221) can possibly facilitate the choice of the appropriate treatment regimen in the future.We conclude that there is a lot of recent development in the area of biomarker-driven targeted therapies and immunotherapies for BTC, which could consequently bring major benefits to patients’ treatment outcomes and quality of life.